The incidence of upper respiratory infections in children is related to the concentration of vanadium in indoor dust aggregates - Prokopciuk, Nina; Taminskiene, Vaida; Vaideliene, Laimute; Juskiene, Izabele; Svist, Vitalija; Valiulyte, Indre; Valskys, Vaidotas; Valskiene, Roberta; Valiulis, Algirdas; Aukstikalnis, Tomas; Vaidelys, Lukas; Butikis, Mindaugas; et al. (Frontiers in Public Health, 2024)
Background. It has been reported that the disease-initiated and disease-mediated effects of aerosol pollutants can be related to concentration, site of deposition, duration of exposure, as well as the specific chemical composition of pollutants. Objectives. To investigate the microelemental composition of dust aggregates in primary schools of Vilnius and determine trace elements related to acute upper respiratory infections among 6- to 11-year-old children. Methods. Microelemental analysis of aerosol pollution was performed using dust samples collected in the classrooms of 11 primary schools in Vilnius from 2016 to 2020. Sites included areas of its natural accumulation behind the radiator heaters and from the surface of high cupboards. The concentrations of heavy metals (Pb, W, Sb, Sn, Zr, Zn, Cu, Ni, Mn, Cr, V, and As) in dust samples were analysed using a SPECTRO XEPOS spectrometer. The annual incidence rates of respiratory diseases in children of each school were calculated based on data from medical records. Results. The mean annual incidence of physician-diagnosed acute upper respiratory infections (J00-J06 according to ICD-10A) among younger school-age children was between 25.1% and 71.3% per school. A significant correlation was found between vanadium concentration and the number of episodes of acute upper respiratory infections during each study year from 2016 to 2020. The lowest was r=0.67 (p=0.024), and the highest was r=0.82 (p=0.002). The concentration of vanadium in the samples of dust aggregates varied from 12.7 to 52.1 parts per million (ppm). No significant correlations between the other trace elements and the incidence of upper respiratory infections were found, which could be caused by a small number of study schools and relatively low concentrations of other heavy metals found in the samples of indoor dust aggregates. Conclusions. A significant and replicable correlation was found between the concentration of vanadium in the samples of natural dust aggregates collected in primary schools and the incidence of acute upper respiratory infections in children. Monitoring the concentration of heavy metals in the indoor environment can be an important instrument for the prevention and control of respiratory morbidity in children.